TECHNIQUES FOR EFFECTIVE COUNSELING WITH DISCONFICENT STUDENTS - Salsabila Nasution; Rezki Hariko; Yeni Karneli (Program Studi Bimbingan dan Konseling FKIP UMSU, 2023)
Confidence is a belief that exists in humans who perceive life's challenges to be faced. Confidence has a very meaningful role in the process of life. One can miss various opportunities if one is not confident. The crisis of confidence is one of the biggest obstacles to action. Not only hesitate to act, even to the point of not acting. The purpose of this study is to provide tips for counselors in providing counseling to students who lack self-confidence. This research method is a literature study by collecting a number of literature in the form of books, journals that are relevant to the problem and objectives. The result of this research is that counseling can increase students' self-confidence if they pay attention to the quality of the counselor's relationship with the client. The quality of the counselor's relationship with the client plays a very important role which can be seen from the counselor's ability in four, congruence, unconditional positive attention, and respect for students.